Canine nodal marginal zone lymphoma: Descriptive insight into the biological behaviour. (4th December 2017) - Cozzi, M.; Marconato, L.; Martini, V.; Aresu, L.; Riondato, F.; Rossi, F.; Stefanello, D.; Comazzi, S.
Abstract : Canine nodal marginal zone lymphoma (nMZL) is classified as an indolent lymphoma. Such lymphomas are typified by low mitotic rate and slow clinical progression. While the clinical behaviour of canine splenic MZL has been described, characterized by an indolent course and a good prognosis following splenectomy, there are no studies specifically describing nMZL. The aim of this study was to describe the clinical features of and outcome for canine nMZL. Dogs with histologically confirmed nMZL undergoing a complete staging work‐up (including blood analysis, flow cytometry [FC] on lymph node [LN], peripheral blood and bone marrow, imaging, histology and immunohistochemistry on a surgically removed peripheral LN) were retrospectively enrolled. Treatment consisted of chemotherapy or chemo‐immunotherapy. Endpoints were response rate (RR), time to progression (TTP) and lymphoma‐specific survival (LSS). A total of 35 cases were enrolled. At diagnosis, all dogs showed generalized lymphadenopathy. One‐third was systemically unwell. All dogs had stage V disease; one‐third also had extranodal involvement. The LN population was mainly composed of medium‐sized CD21+ cells with scant resident normal lymphocytes. Histology revealed diffuse LN involvement, referring to "late‐stage" MZL. Median TTP and LSS were 149 and 259 days, respectively. Increased LDH activity and substage b were significantly associated with a shorter LSS. Dogs with nMZL may show generalized lymphadenopathy and an advanced disease stage. Overall, the outcome is poor, despite the "indolent" designation. The best treatment option still needs to be defined.